LAJU PRODUKTIVITAS PRIMER PERAIRAN RAWA KONGSI KECAMATAN PATUMBAK KABUPATEN DELI SERDANG PROVINSI SUMATERA UTARA (The Rate of Aquatic Primary Productivity in Kongsi Swamp Patumbak District of Deli Serdang Regency North Sumatra) - Dinarta Pardede; Ternala Alexander Barus; Rusdi Leidonald (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2016)
The Rate of Aquatic Primary Prod uctivity (RAPP) is the formation of organiccompounds from inorganic compounds with the aid of sunlight and chlorophyll. KongsiSwamp is stagnant water system utilized by people for agriculture, livestock, fishingand waste disposal that cause a negative effect. This study aims to know RAPP in RawaKongsi and to know RAPP relationship with chlorophyll-a and physical chemistryparameters of water. The study took place from February until March 2016. Thesampling location choosed by purposive sampling which divided into 4 stations basedon different activities. The analysis were method water quality, chlorophyll-a, primaryproductivity and Pearson correlation. The results of water quality analysis showed thatKongsi swamp was moderately polluted based on the average of DO 2,28 mg/L, thevalue average of aquatic primary productivity Kongsi swamp 487,968 mgC/m3/hari,levels trophic based on the value average of chlorophyll-a 2.461 mg/m3 including thecategory of low fertility (oligotrophic). The correlation between primary productivitywith chlorophyll-a and chemical physics of water in Kongsi Swamp is very strong.Keywords: Aquatic Primary Productivity, Chlorophyl-a, Kongsi Swamp, Water Quality